Nodal Downstaging of Esophageal Cancer After Neoadjuvant Therapy: A Cohort Study and Meta‐Analysis - Feng Su; Xu Huang; Jun Yin; Hang Tang; Lijie Tan; Yaxing Shen (Cancer Medicine)
ABSTRACT Background In esophageal cancer, the ypN0 status after induction therapy could be categorized into two primary groups: “natural N0” (cN0/ypN0) and “down‐staged N0” (cN+/ypN0). The assessment of cN status is typically based on clinical imagination or pathological regression. However, there is no standardized method for evaluating cN/ypN status. This study aims to investigate the prognosis of patients with cN+/ypN0 using both assessment methods through a cohort study and meta‐analysis. Methods A prospectively maintained database encompassing esophageal cancer patients undergoing induction therapy followed by radical esophagectomy was comprehensively reviewed. The prognostic significance of cN+/ypN0 across two evaluation methods was quantified. Additionally, a meta‐analysis using data from previous studies was conducted. Results 578 patients were identified from the cohort analysis, with 342 classified as ypN0 and 236 as ypN+. When evaluated with clinical imagination, patients with cN+/ypN0 had survival outcomes comparable to those with natural N0 but significantly better than those with ypN+ (p < 0.001). Using pathological nodal regression, cN+/ypN0 patients showed superior overall survival compared to ypN+ patients (p = 0.0043), although their disease‐free survival was notably inferior to that of natural N0 patients (p = 0.0088). A meta‐analysis of 20 previous studies confirmed the prognostic value of cN+/ypN0 status in both clinical imagination and pathological regression. Conclusions For esophageal cancer patients receiving neoadjuvant, cN+/ypN0 status, assessed through both clinical imagination and pathological regression, serves as a significant prognostic factor. It holds precedence over ypN+ yet falls short of the natural N0. The pre‐treatment categorizations warrant recognition as a novel and pertinent staging metric.